An empirical investigation of the impact of foreign direct investment on economic growth in Ethiopia - Melkamu Wondimu (Cogent Economics & Finance, 2023)
The main objective of this study is to empirically investigate the impact of foreign direct investment on economic growth of Ethiopia by using a time series data for the period 1992-2019. Other explanatory variables like trade openness, human capital, national saving and gross capital formation were incorporated in the model. For the purpose of undertaking the study, Autoregressive Distributed Lag (ARDL) econometric model was employed. Moreover, a Toda-Yamamoto Causality test was performed to identify the direction of the causality between economic growth and foreign direct investment. Findings from the study show that, both in the short run and long run, foreign direct investment has a positive and significant impact on economic growth. As an outcome of Toda-Yamamoto Causality test shows, there is a unidirectional causality running from economic growth to foreign direct investment. On the basis of the findings, recommendations are made for the government authorities to expand infrastructural facilities for enabling a free movement of the investors to the remote and marginalized areas to further expand investment activities that result in higher economic growth.
Keywords: 330; Autoregressive Distributed Lag; economic growth; foreign direct investment